ANALISIS PERAN KREDIT BANK TERHADAP PERTUMBUHAN EKONOMI (STUDI KASUS PADA 12 PROVINSI DI INDONESIA) - Ella Salvia Purnama (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research to know and to analyze the role of credit, labor, investment, and infrastructure on economic growth. This study will analyze the influence of variable bank credit, labor, investment and infrastructure on economic growth in 12 provinces in Indonesia, which is central Sulawesi, south Sulawesi, north Sulawesi, southeast Sulawesi, west Sulawesi, Gorontalo, Nusa southeastern west, Nusa east southeast, Maluku, north Maluku, Papua, and west Papua. This research uses the quantitative. Population to research this is all the bank located in Indonesia. Types of data on in this research the kind of data that used is taken from secondary data.Model regression data panel is regression using data Panel. Data panels (Panel pooled data) was a combination of data cross section and time series. Based on the research done and discussion that has been done so a conclusion can be drawn as follows: 1 the analysis shows that the, labor, investment and infrastructure influential on economic growth. The results of the analysis it can be seen that value the coefficients determination (R2) receive is 0,539. It means variable economic growth influenced by 53,9 % by credit, labor, investment and infrastructure while the rest 46,1 % described by other variables that did not discuss in this research.Keywords: bank credit and economic growth